The impact of source credibility and information quality on healthcare consumers’ attitudes: the moderating role of perceived severity - Chen, Fan; Wang, Ying (Frontiers in Public Health, 2025)
In the context of market competition, the acceptance of a doctor’s opinion by healthcare consumers depends on the source credibility and the information quality. In particular, differences in individual healthcare consumers’ perceptions of their illnesses may affect the choice of trusting the source credibility or the content of the information, i.e., even for minor ailments, they may prefer to trust a doctor with authority, regardless of the quality of the content of the information. By enhancing the perceived authority of doctors and the trustworthiness of information quality, communication effectiveness can be targeted to reduce consumer anxiety and eliminate communication barriers or upsets within a limited consultation time. In order to explore the underlying mechanisms of the association between source credibility and information content and consumers’ subjective attitudes, this paper takes healthcare services as an example, uses social support theory as the background, and based on the exhaustive likelihood model, firstly, applies structural equation modelling to examine the mechanism of the interaction’s influence on consumers’ attitudes, and then applies the multi-cluster structural model in conjunction with the protective motivation theory to examine the moderating effect of the perceived seriousness of the interaction on the influencing mechanism. The study found that interaction positively affects service satisfaction indirectly through the mediation of information quality and source credibility, and that perceived severity moderates the relationship between information quality and source credibility and consumer attitudes. In addition, the findings of the study provide theoretical guidance for the future exploration of the influence mechanism of consumer attitudes, and provide important insights into the innovation of online healthcare service models in the digital era.